(untitled) (Journal of Imam Al-Kadhim College, 2026)
This study examines the Verse of Proclamation (Qur’an 5:67) through an analytical exegetical approach that integrates Qur’anic sciences, linguistic analysis, rhetorical examination, and the study of circumstances of revelation (asbāb al-nuzūl). Given that Surah Al-Ma’idah is among the last chapters revealed, the verse under discussion occupies a pivotal position in the final stage of the Islamic message and reflects a decisive moment in the history of Islam. The research demonstrates that the conditional structure in the verse—“And if you do not, then you have not conveyed His message”—indicates that the command given to the Prophet (peace be upon him and his family) concerns a matter of exceptional gravity, such that neglecting it would amount to the failure of conveying the entire divine mission. Through linguistic and rhetorical analysis, the study highlights the force of the imperative form “convey” (balligh), the exclusive address “O Messenger”, and the divine assurance of protection—“Allah will protect you from the people”—all of which underscore the sensitivity and significance of the commanded proclamation. By surveying narrations transmitted in both Shiʿi and Sunni exegetical sources, the study concludes that the verse was revealed in connection with the event of Ghadir Khumm, where the Prophet publicly proclaimed the authority (wilāyah) of Imam ʿAli ibn Abi Talib (peace be upon him). The research further establishes a close thematic relationship between the Verse of Proclamation, the Verse of Wilayah (5:55), and the Verse of the Completion of Religion (5:3), revealing a coherent Qur’anic framework affirming the principle of leadership after the Prophet. Accordingly, the study affirms that the Verse of Proclamation is not related to a subsidiary legal ruling or a confrontation with disbelievers, but rather addresses a foundational issue essential to the preservation and continuity of the Islamic message. It thus represents a decisive Qur’anic declaration marking the completion of the religion and the culmination of the Prophet’s mission.